Grammatical Cohesion Analysis in the Short Story “The Devoted Friend” by Oscar Wilde - Kadek Novi Krisna Dewi; Gede Irwandika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
This study examined about grammatical cohesion that applied in the short story “The Devoted Friend. The aims of the research is to identify the different forms of grammatical cohesiveness and their applications in the short narrative